Mapping research in Socio-pragmatic linguistics on food vloggers on YouTube: A bibliometric analysis - Rahman, Fauzi; Rafli, Zainal; Anwar, Miftahulkhairah (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2024)
The phenomenon of food vloggers sharing their culinary experiences through videos presents an interesting area for sociopragmatic studies. This research focuses on understanding the social interactions and pragmatic contexts within food vlogging content. Specifically, the study aims to map the development of sociopragmatic research on the YouTube platform in relation to food vlogging. Using qualitative methods and bibliometric analysis, this study identifies and analyzes publications related to sociopragmatics and food vlogging from electronic databases such as Web of Science, Scopus, and Google Scholar. Keywords such as